2012
DOI: 10.1029/2011gl050282
|View full text |Cite
|
Sign up to set email alerts
|

Chemical controls on ozone deposition to water

Abstract: [1] The deposition of ozone to seawater is known to be controlled by a variety of physical and chemical processes. At low wind speeds chemical loss is comparatively more important than loss due to physical processes. We have determined experimentally the relationship between ozone deposition velocity and concentration of iodide and dissolved organic matter in water buffered at seawater pH (8.0). The concentrations of both species used in this study are representative of those encountered in coastal and oceanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…13 Observed oceanic O 3 deposition velocities measured by eddy covariance from both fixed tower platforms 41,55 or by turbulent aircraft measurements 40,56 are approximately double that calculated from the presence of iodide alone in coastal waters. 25,32 This is consistent with recent laboratory measurements by Martino et al, 33 who demonstrated that natural DOC (sourced from the Suwannee River) and iodide at naturally occurring concentrations contribute similarly to the chemical enhancement of ozone deposition to surface waters. As shown in Figure 1 25,57 Thus, our laboratory measurements suggest that an additional components of coastal seawater, most likely DOC, is an important chemical control of O 3 deposition over coastal waters.…”
Section: ■ Introductionsupporting
confidence: 90%
“…13 Observed oceanic O 3 deposition velocities measured by eddy covariance from both fixed tower platforms 41,55 or by turbulent aircraft measurements 40,56 are approximately double that calculated from the presence of iodide alone in coastal waters. 25,32 This is consistent with recent laboratory measurements by Martino et al, 33 who demonstrated that natural DOC (sourced from the Suwannee River) and iodide at naturally occurring concentrations contribute similarly to the chemical enhancement of ozone deposition to surface waters. As shown in Figure 1 25,57 Thus, our laboratory measurements suggest that an additional components of coastal seawater, most likely DOC, is an important chemical control of O 3 deposition over coastal waters.…”
Section: ■ Introductionsupporting
confidence: 90%
“…The Fairall parameterisation, including chemical reactivity was further developed based on the laboratory studies [12,17] in which the chemical enhancement of the ozone deposition velocity was quantified for iodide and DOC reactants. The reaction rate for ozone and DOC, k DOCuM-O3 , was calculated by comparing the results from ozone-iodide reactions with the Fairall dry deposition theory and known ozone-iodide reaction kinetics [18] and determining systematic constants for the experimental setup.…”
Section: Model Developmentmentioning
confidence: 99%
“…Combining R a and the rate constant used in Magi et al [18] for sea-surface O 3 -I reactions, we can define the experimental setup in terms of Fairall's dry deposition velocity equation. A surface turbulence term (τ) is required to be combined with R w to replicate the Martino et al [12] experiments. Consequently, the dry deposition velocity to seawater can be written as follows:…”
Section: Model Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Prime candidates for the oceanic reactivity are the iodide ion (I À ) as well as organic constituents (Oh et al 2008). The results of a recent laboratory study indicate that these two reactants are about equally important in determining the deposition velocity of ozone (Martino et al 2012). Most likely, these reactions occur in the ocean surface microlayer or the immediately underlying seawater.…”
mentioning
confidence: 99%